(3Gdaf GdUMaj aj YUQ GdeYdheGJ (B:s (3JMQjQ h cJGHI GdJMbjbGJ h GdCMGOjK GdUMajI (B/s - (3fUQ, MSfj eMeOs; (3YHO GdQMeGfs ((3GdEeGQGJ (B:s (3OGQ GdcJGH GdLGeYj ,s, 2005)
(3GdcJGH gh LRA GdKGfj ef SdSdI echfI ef KdGKI cJH Mhd GdJMQjQ GdUMaj aj YUQ GdeYdheGJ h bO UOQ GdcJGH GdGhd efgG aj GhGNQ YGe (B2002 (3HYfhGf GdJMQjQ GdUMaj aj YUQ GdeYdheGJ GdNHQ GdUMaj h eG gh GdcJGH GdKGfj Mhd JMQjQ h cJGHI GdJMbjbGJ h GdGMGOjK s
(3HHdjhZQGajG (B: (3U(B.389-392s
Keywords: (3GdJMbjb GdUMajs; (3GdUMGaIs; (3GdcJGHIs; (3GdeYdheGJjIs